Dampak Motivasi Kerja Dan Stres Kerja Terhadap Kinerja Karyawan PT. Asuransi Jasa Indonesia (Persero) Kantor Cabang Surabaya : Studi Kasus PT. Asuransi Jasa Indonesia Cab, Surabaya - Dema Erita; Sugiharto Sugiharto; Harsono Teguh; Achmad Daengs GS; Rina Dewi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
So that employees can provide the best service to consumers, it is very important to motivate employees. If providing motivation to employees is less effective then this will have a direct impact on employee performance. High performance can be created if employees feel happy and comfortable at work. Stress is a dynamic condition where an individual is confronted with an opportunity, constraint or demand that is related to what he wants and the results are perceived as uncertain and important. Therefore, the problem of work stress and employee mental health needs to receive serious attention from the leadership. The research method used in this research uses multiple linear regression analysis. Simultaneous testing using the F test shows that there is a real influence between the independent variable and the dependent variable, as evidenced by the Fcount value of 21.382 > Ftable 3.3. In this simultaneous relationship, a coefficient of determination (R²) of 0.613 or 61.3% of the existing data is produced, indicating that the two independent variables, namely work motivation (X₁) and work stress (X₂) are able to explain the variable, namely employee performance confidence (Y). , while the multiple R is 0.783 or 78.3%, which shows that the relationship between the independent variables as a whole and the dependent variable is quite strong. Partially, the work stress variable (X₂) has a significant and dominant effect on employee performance with a tcount of 4.314 > ttable 2.052 and a significant value of 0.000. This means work stress which consists of: excessive workload, work conflict, work frustration, equipment availability, and time constraints.